Metropolitan Regions as Centres of Knowledge and Innovation Creation - Viktorie Klímová; Vladimír Zítek (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Each region can be considered to be an individual regional innovation system. It is possible to distinguish various types of these systems. The approach based on assessment of deficiencies, which are organization thinness, lock-in effect and fragmentation, defines three types of imperfect regional innovation systems. The metropolitan regions are one of these types. These regions can be characterized by above-average research, innovation and patent activity and they are considered innovation centres. But this is not true absolutely; some of them typically have a fragmented innovation system and insufficient linking of its elements. On the basis of theoretical background it is possible to design a group of indicators that characterize this type of regions. The aim of this paper is to find relevant indicators that can be used as a basis for the definition of metropolitan regional innovation systems in the Czech Republic. Using the point method and cluster analysis, the Czech metropolitan regions on the NUTS3 level can be defined. Especially the Capital city Prague and the South-Moravian Region (encompassing the second biggest city Brno) can be defined as metropolitan regions. Other NUTS3 regions that can be considered metropolitan regions are the Pardubice, Central Bohemian, Pilsen and Liberec Regions.
Keywords: R11; O31; 330; regional innovation system; knowledge; innovation; region; Czech Republic; metropolitan region